Upcycling Spent Selective-Catalytic-Reduction Catalyst to Produce Titanium Carbide Through Molten-Salt Electrolysis - Weigang Cao; Qi Zhu; Long Zheng; Jiahao Jin; Xiangpeng Li; Yanan Xu (Crystals)
The molten-salt electrolytic method was employed to recycle spent SCR catalyst to prepare TiC compound. A systematic investigation has been carried out through thermodynamic calculation and experimental analysis. The effects of graphite content, cell voltage, electrolyzing temperature, and electrolyzing time on electrolytic products were explored. The results show that a suitable amount of graphite content, high cell voltage, and a high electrolyzing temperature are beneficial to promote the formation of TiC compounds. It has also been found that the electroreduction of spent SCR catalyst/graphite can completely transform it into TiC compound in a relatively short time. The final electrolytic product is confirmed to be a solid solution of (Ti, W, Si, V)C. Meanwhile, the electrolytic process and reaction mechanism were investigated through the analysis of intermediates and the thermodynamic calculation. The electrolytic product has a potential application as reinforcement in metal matrix, which is a high additional-value utilization for spent SCR catalysts.